Production of Shale Oil and Gas in the US: Current Status and Prospects - N. A. Ivanov; N. N. Poussenkova; A. V. Sokolov (Georesursy, 2024)
The article analyzes resilience factors of tight oil and gas production in the USA. The US is the only country in the world that currently produces shale hydrocarbons on a commercial scale, though other petroleum states try to emulate their success in this sphere. The American shale revolution became possible due to a massive application of hydrofracking in combination with horizontal drilling to produce tight oil and gas. Therefore, the mighty technological potential of the American petroleum sector became the key success factor of the US shale revolution. However, technological breakthroughs are necessary, but not sufficient for ensuring a stable development of the shale industry. Of particular importance is the institutional framework of the US shale sector that is characterized by an efficient system of subsurface use, a powerful financial and industrial base, a long-term strategy of the state support for R&D, a reasonable fiscal policy, a transparent regulation, as well as a competitive and diversified structure of the shale sector. This unique combination of factors will be extremely difficult to replicate in other countries. When constructing long-term scenarios of oil and gas production, the US Energy Information Administration proceeds from the key assumptions of resource availability and rates of improving production technologies. The analysis of the shale phenomenon permits to conclude that these two factors are interconnected – the continuous technological progress of the sector ensures the enhanced oil and gas recovery ratio. As a result, the production growth is accompanied by the growth of resource availability. The limits to this trend are not visible yet, and, therefore, it means that the upside potential of shale production is not exhausted.